1985
DOI: 10.1113/jphysiol.1985.sp015613
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of long‐term potentiation in the rat dentate gyrus by post‐trial stimulation of the reticular formation.

Abstract: SUMMARY1. The possibility that post-trial stimulation of the mesencephalic reticular formation (m.r.f.) may modulate long-term potentiation (l.t.p.) at the perforant path to dentate granule cell synapses was studied in freely moving rats.2. Extracellular potentials evoked in the dentate gyrus by test pulses to the perforant path were recorded before and at various delays after a series of highfrequency stimulus trains to the perforant path (ten trains of eight pulses at 400 Hz, delivered at 5 min intervals).3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…For example, LTP in the dentate gyrus decays more quickly in old than in young rats (Barnes, 1979), and the difference in LTP decay rates is similar to the difference observed between old and young rats in their forgetting rates of spatial information (Barnes and McNaughton, 1985). Furthermore, postevent electrical stimulation of the mesencephalic reticular formation, a maneuver that facilitates memory (e.g., Deweer, 1976;Dekeyne et al, 1987), has been shown to facilitate and prolong LTP in the dentate gyrus (Bloch and Laroche, 1985) and to promote long-term maintenance of hippocampal associative cell responses to a CS in classical conditioning (Bloch and Laroche, 1981). In addition, protein synthesis inhibitors prevent the formation of longterm memory (see Gibbs and Ng, 1977;Dunn, 1980;Rosenzweig and Bennett, 1984, for reviews) and suppress the late phases of LTP in the dentate gyrus (Krug et al, 1984;Otani et al, 1989).…”
Section: Discussionmentioning
confidence: 58%
“…For example, LTP in the dentate gyrus decays more quickly in old than in young rats (Barnes, 1979), and the difference in LTP decay rates is similar to the difference observed between old and young rats in their forgetting rates of spatial information (Barnes and McNaughton, 1985). Furthermore, postevent electrical stimulation of the mesencephalic reticular formation, a maneuver that facilitates memory (e.g., Deweer, 1976;Dekeyne et al, 1987), has been shown to facilitate and prolong LTP in the dentate gyrus (Bloch and Laroche, 1985) and to promote long-term maintenance of hippocampal associative cell responses to a CS in classical conditioning (Bloch and Laroche, 1981). In addition, protein synthesis inhibitors prevent the formation of longterm memory (see Gibbs and Ng, 1977;Dunn, 1980;Rosenzweig and Bennett, 1984, for reviews) and suppress the late phases of LTP in the dentate gyrus (Krug et al, 1984;Otani et al, 1989).…”
Section: Discussionmentioning
confidence: 58%
“…All of the tetanization parameters were otherwise identical. Indeed, it is noteworthy that many other previous studies using relatively short baselines also found dentate LTP to be decremental (Racine et al, 1983;Bloch and Laroche, 1985; de Jonge and Racine, 1985). To confirm that the length of the baseline recordings on the day of tetanization was a crucial protocol difference, three additional animals were given the short-baseline 50T paradigm.…”
Section: Sensitivity Of Stable Ltp To Variables On the Day Of Tetanizmentioning
confidence: 89%
“…During wakefulness, acquired information is stored temporarily in the hippocampus, amygdala, and some cortical and subcortical areas; during subsequent sleep, these areas are reactivated to "consolidate" acquired information into more permanent storage in the neocortex (Hennevin and Hars, 1985;Buzsaki, 1989Buzsaki, , 1996Pavlides and Winson, 1989;Wilson and Mc-Naughton, 1994;Datta, 1999). These temporary storage areas would require a reactivating cue and/or triggering input during sleep (Bloch and Laroche, 1985;Bliss and Collingridge, 1993;Datta, 1999). The exact anatomical and physiological source of this cue and/or triggering input during natural sleep remains to be identified.…”
mentioning
confidence: 99%